TRANSLATION, CULTURAL ADAPTATION, AND EVIDENCE OF INSTRUMENT VALIDITY FOR A MORPHOLOGICAL EXAMINATION PERFORMED IN CHILDREN WITH AUTISM SPECTRUM DISORDER - Thais Arbocese Zanolla; Eduardo Perrone; Rodrigo Ambrosio Fock; Daniela Bordini; Helena Paula Brentani; Ana Beatriz Alvarez Perez; Decio Brunoni (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: For every 100 random children diagnosed with autism, at least 20 have morphological abnormalities, often associated with syndromes. Brazil does not have a standardized and validated instrument for morphological physical examination. This study aimed to translate into Brazilian Portuguese and culturally adapt the clinical signs described in the Autism Dysmorphology Measure, as well as validate the instrument in a sample of children with autism. Methods: The original instrument was translated, culturally adapted, and published in full, following traditional procedures for translation, back-translation, and terminology adaptation according to the Nomina Anatomica. The sample included 62 children from a published multicenter study, with intelligence quotient between 50-69, of both genders, with chronological age between 3-6 years. Two clinical geneticists performed the morphological physical examination, which consisted of investigating 82 characteristics assessing 12 body areas. We used Cohen's Kappa coefficient to evaluate the agreement between the two observers. Results: The final version of the instrument - translated into Brazilian Portuguese and culturally adapted - showed high agreement between the two observers. Conclusions: The translated instrument meets all international criteria, and minor anomalies and their clinical descriptions were standardized and are recognizable for physicians not specialized in genetics.